What can modern plastic surgery offer postmenopausal women? - Jankau, Jerzy; Ankiewicz, Aleksandra; Kuczyński, Maciej (Menopause Review/Przegląd Menopauzalny, 2008)
Passage of time has to be accepted. Most people pass it without consultation with a plastic surgeon, and get old with dignity. There are however many women who need the help of plastic surgery. Together with their gynaecologists we can offer them various kinds of expected surgery which help them in their postmenopausal days. This work presents some of the procedures available for women in the postmenopausal period.